2021
DOI: 10.2147/rmhp.s259680
|View full text |Cite
|
Sign up to set email alerts
|

Refugee Health During the Covid-19 Pandemic: A Review of Global Policy Responses

Abstract: Refugees and displaced persons have been severely affected by the Covid-19 pandemic. Yet findings from this narrative review reveal that the health needs of refugees have been largely neglected within global healthcare responses. Such gaps include: (1) responding to the needs of refugees in camps and detention centers; (2) providing adequate public health information; (3) providing access to healthcare and mental health services; (4) and including refugees as decision-makers within health responses. More resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The findings of this study revealed that a decrease in queues, waiting for hours, delivery of drugs through VHTs, proximity to health facilities, access to public transport, ability to reach the facilities, access to necessities like food and the reception at the health facilities facilitated access to TB or HIV/AIDS services. It is important to note that during the pre-COVID-19 period, long queues and waiting hours were articulated by some studies as negatively affecting access to ART care ( Knipper, Sedas, and Keshavjee, 2021/03/26/2021 , Lupieri, 2021 ). On the other hand, restrictions on public transport, high transport costs, unemployment and subsequent poverty were barriers to access to TB or HIV/AIDS services.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study revealed that a decrease in queues, waiting for hours, delivery of drugs through VHTs, proximity to health facilities, access to public transport, ability to reach the facilities, access to necessities like food and the reception at the health facilities facilitated access to TB or HIV/AIDS services. It is important to note that during the pre-COVID-19 period, long queues and waiting hours were articulated by some studies as negatively affecting access to ART care ( Knipper, Sedas, and Keshavjee, 2021/03/26/2021 , Lupieri, 2021 ). On the other hand, restrictions on public transport, high transport costs, unemployment and subsequent poverty were barriers to access to TB or HIV/AIDS services.…”
Section: Discussionmentioning
confidence: 99%
“…WelcomeRefugees 2021 ). According to studies, refugees are more prone to negative mental health outcomes than the general population ( Filler et al, 2021 , Lupieri, 2021 ). Feelings of insecurity, discrimination, and language barriers could all be contributing factors ( Hadfield et al, 2017 , Kirmayer et al, 2011 , Clarke et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Background experiences related to dislocated education and post-traumatic stress disorder may impair refugees’ ability to understand COVID-19 messages [ 11 ]. Moreover, governments have frequently failed to provide adequate public health communication to refugee groups [ 11 , 12 ]. Although government advisory groups have been established to involve CALD leaders in pandemic responses [ 13 ], such bodies have not adequately included refugees [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, governments have frequently failed to provide adequate public health communication to refugee groups [ 11 , 12 ]. Although government advisory groups have been established to involve CALD leaders in pandemic responses [ 13 ], such bodies have not adequately included refugees [ 12 ]. By presenting culturally biased models of health information, governments risk reinforcing stigma and further isolating minority groups [ 14 ].…”
Section: Introductionmentioning
confidence: 99%